An Interactive Method for Fuzzy Multiobjective Nonlinear Programming Problems - Kanaya, Ziyad A. (Journal of King Abdulaziz University. Science, 2010)
This paper presents a solution method for multiobjective nonlinear programming problems with fuzzy parameters in the objective functions. This method is based on interactive cutting-plane algorithm. Also, the stability set corresponding α-Pareto optimal solution which is obtained by using this method is investigated. The method is illustrated by a numerical example يقدم هذا البحث لحل مسائل البرمجة غير الخطية المتعددة الأهداف مع وجود وسائط ضبابية في دوال الهدف، و تعتمد الطريقة على خوارزمية المستوى القاطع التفاعلية. كما تم التحقق في مجموعة الاستقرار المرافقة لحل α- بارتو الأمثل الذي حصلنا عليه باستخدام تلك الطريقة. و الطريقة المقدمة موضحة بمثال عددي.